Comparative Analysis in life cycle assessment of innovative recycling processes for end-of-life c-Si PV panels - Chung Jae Shik; 박보경; Bora Seo; Jae Young Kim (k-water, 2019)
A recent development in renewable energy enabled a reduction of fossil fuel usage whereas so-called energy waste such as end-of-life batteries became an emerging issue in waste management at the same time. In this study, a series of life cycle assessment (LCA) of various treatment processes for end-of-life monocrystalline-Si photovoltaic panel (c-Si PV) was conducted under various recycle and disposal scenarios to quantify the environmental impact of the each, or combined processes within the well-defined system boundary; an innovative recycling process (FRELP) was benchmarked to further reduce the environmental impact via modification of sub-processes (i.e., acid leaching and resource recovery). More than 80% of the global warming potential was accounted for by transport, incineration, and ash treatment processes and the environmental impacts could be effectively reduced by replacing the conventional solvents (i.e., nitric acid) into environmentally friendly alternatives (e.g., protic solvents) while environmental credits from recovered materials were optimized by enhancing the purity of recovered metals (e.g., silver and copper). The net present value (NPV) of the process is found to be dependent on the PV waste generation rate and their collection (i.e., scale-dependency) as well as the advancement of recycling technologies. A laboratory-scale experiment with respect to the per unit production cost is currently under investigation for the validation purpose.
Keywords: Energy waste; End-of-life PV panel; LCA; Recycling; Resource recovery